Theoretical Frameworks for Integrating Sustainability Factors into Institutional Investment Decision-Making - Alhamis, Innocents (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2024)
This paper explores key theoretical frameworks instrumental in understanding the relationship between sustainability and institutional investment decisions. The study identifies and analyzes various theories, including Behavioral Finance Theory, Modern Portfolio Theory, Risk Management Theory, and others, to explain how sustainability considerations increasingly influence investment choices. By examining these frameworks, the paper highlights how investors integrate Environmental, Social, and Governance (ESG) factors to optimize financial outcomes and align with broader societal goals.